Significado regional dos depósitos neogénicos continentais da área de Vila de Rei (Portugal Central) - Barra, A. P. (2010)
In the Vila de Rei area (Central Portugal) the continental deposits of the Lower Tagus Tertiary Basin lay upon the pediment of the Portuguese Central Chain. Three conglomerate units are recorded from the base upwards, separated by regional or basinal unconformities; Conglomerados de Rio de Moinhos (RM); Conglomerados de Serra de Almeirim (SA) and Conglomerados de Vila de Rei (VR). The first two units (RM and SA) have been sites of gold exploitation in huge open pit mines probably during Roman colonisation times. The contact of this units, on the Paleozoic basement or on the Paleogene unit Grés de Monsanto, is unconform, defining in both limits a large nondepositional and/or erosional hiatus. Those conglomerates seal the sedimentation of the Lower Tagus Tertiary Basin along its northern border. Taking into account the significance assigned to their basinal unconformity limits, the uplift of the Portuguese Central Chain, and the fact of this continental units yielded no fossils with chronostratigraphic significance, they have been considered ranging from Upper Miocene to the beginning of the Quaternary. Finally, a lithostraligraphic equivalence with the Neogenic units of the Bierzo and Duerna basins (NW of the Iberian Peninsula), where exploitations from Roman times are also evident, is presented.